The chromatin and single-cell transcriptional landscapes of CD4 T cells in inflammatory bowel disease link risk loci with a proinflammatory Th17 cell population - Medina, Tiago S.; Murison, Alex; Smith, Michelle; Kinker, Gabriela S.; Chakravarthy, Ankur; Vitiello, Glauco A. F.; Turpin, Williams; Shen, Shu Yi; Yau, Helen L.; Sarmento, Olga F.; Faubion, William; Lupien, Mathieu; et al. (Frontiers in Immunology, 2023)
The imbalance between Th17 and regulatory T cells in inflammatory bowel diseases (IBD) promotes intestinal epithelial cell damage. In this scenario, T helper cell lineage commitment is accompanied by dynamic changes to the chromatin that facilitate or repress gene expression.Here, we characterized the chromatin landscape and heterogeneity of intestinal and peripheral CD4 T cells from IBD patients using in house ATAC-Seq and single cell RNA-Seq libraries.We show that chromatin accessibility profiles of CD4 T cells from inflamed intestinal biopsies relate to genes associated with a network of inflammatory processes. After integrating the chromatin profiles of tissue-derived CD4 T cells and in-vitro polarized CD4 T cell subpopulations, we found that the chromatin accessibility changes of CD4 T cells were associated with a higher predominance of pathogenic Th17 cells (pTh17 cells) in inflamed biopsies. In addition, IBD risk loci in CD4 T cells were colocalized with accessible chromatin changes near pTh17-related genes, as shown in intronic STAT3 and IL23R regions enriched in areas of active intestinal inflammation. Moreover, single cell RNA-Seq analysis revealed a population of pTh17 cells that co-expresses Th1 and cytotoxic transcriptional programs associated with IBD severity. Altogether, we show that cytotoxic pTh17 cells were specifically associated with IBD genetic variants and linked to intestinal inflammation of IBD patients.